Biology - Mader, Sylvia S. (McGraw-Hill Higher Education, 2004)
Biology is now a tightly knit text that covers the concepts and principles of biology from the structure and function of the cell to the organization of the biosphere. It draws upon the entire world of living things to bring out an evolutionary theme that is introduced from the start. The concept of evolution is necessary to understanding the unity and diversity of life and serves as a background for the study of ecological principles. Modern ecological problems, including the biodiversity crisis, are stressed throughout the text.